Optimal Pricing and Information Provision in Supply Chain with Consumers' Risk Perception. Issue 4 (16th March 2021) - Huang, Rongji; Nie, Tengfei; Zhu, Yangguang
ABSTRACT: Emergency management plays an increasingly important role in the context of China's economic transformation. This article studies the impact of risk perception consumer behavior on pricing strategies of the supplier and the retailer in a dyadic supply chain with emergency-dependent demand. The supplier, as a Stackelberg leader, specifies the wholesale price to the retailer, based on which, the retailer, who faces a market with an emergency, makes the optimal retail price as a response. In this setting, consumers are loss-averse and their utilities vary with the type and the intensity of emergency due to consumers' risk perception behavior. In addition, two types of information, consumer's demand and emergency intensity, are assumed to be possessed by the retailer and the supplier, respectively. How information sharing affects both sides' pricing strategies is also analyzed in this article.